The Mu2e Experiment - Bernstein, Robert H. (Frontiers in Physics, 2019)
The Mu2e experiment will measure the charged-lepton flavor violating (CLFV) neutrino-less conversion of a negative muon into an electron in the field of a nucleus. The conversion process results in a monochromatic electron with an energy of 104.97 MeV, slightly below the muon rest mass. The goal of the experiment is to improve the previous measurement by four orders of magnitude and reach of a SES (single event sensitivity) of 3 x 10^-17 on the conversion rate, a 90% CL of 8 x 10^-17, and a 5sigma discovery reach at 2 x 10^-16. The experiment goal is obtained with a intense pulsed negative muon beam. The pulsed beam is essential to reducing backgrounds. The other essential element is a sophisticated magnetic system composed of three consecutive solenoids to form the muon beam. Mu2e will use an aluminum target and examine 10^18 stopped muons in three years of running. The Mu2e experiment is under design and construction at the Fermilab Muon Campus. The experiment will begin data-taking near the end of 2020 with 3 years of running from 2021 to 2023. Upgrades to other materials than aluminum are already planned. This article is written specifically for younger researchers to bridge the gap between conference presentations and detailed design reports, and examines issues not covered in the former without the details of the latter.